PENGARUH ATMOSFER TOKO, LOKASI TOKO DAN DISPLAY PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO RAJA GROSIR KOTA BIMA - Putri, Sulas Ade; Purnama, Ita; Amirulmukminin, Amirulmukminin (Jurnal Manajemen, 2024)
It is very important for a business or business to be able to offer advantages to consumers with the aim of attracting consumers to decide to buy the products or services offered. There are many aspects that can drive consumer purchasing decisions, including the store atmosphere, store location and product displays offered at the store. The purpose of this research is to determine the shop atmosphere, shop location and product displays on purchasing decisions at the Raja Grosir Shop, Bima City. The research instrument used was a Likert scale questionnaire. Population in this research The population used in this research is all consumers who have purchased products at the Raja Grosir Shop in Bima City whose exact number is not known (unknown population). To determine the number of samples in the unknown population, the Cochran formula is used and a sample is obtained. as many as 96 people. The sampling technique used in this research was purposive sampling. Research data was collected by observation, questionnaires and literature study and then analyzed by hypothesis testing, t test and f test. The research results show that the shop atmosphere, shop location and shop displays partially and simultaneously influence purchasing decisions at the Raja Grosir Shop in Bima City.